Profiles of Sports Injury Locations and Causes among Game Sport Athletes - Hafidz Mukti Ramadhan; Aryadi Rachman (Media Ilmu Keolahragaan Indonesia, 2025)
The purpose of this study was to identify the locations and contributing factors of sports-related injuries among PORPROV contingent athletes from Banjarbaru City. This study employed a descriptive survey method. The population consisted of 203 PORPROV contingent athletes from Banjarbaru City who participated in various game sports. Data were collected using a structured survey instrument to determine the sites and causes of sports injuries experienced during training and competition. The results showed that the lower extremities, particularly the ankle, were the most frequently injured body parts. Ankle injuries accounted for 40.54% of injuries occurring during training and 46.15% of injuries sustained during competition. The main causes of injuries during training were intrinsic factors, especially incorrect movement techniques, which contributed to 39.33% of injury cases. During competition, injuries were commonly caused by intrinsic collisions, improper movement techniques, insufficient warm-up, and lack of rest, each contributing equally at 21.74%. The findings indicate that sports-related injuries among PORPROV contingent athletes predominantly affect the lower extremities, with intrinsic factors being the primary contributors to injury occurrence. These results highlight the importance of proper movement techniques, adequate warm-up, and sufficient recovery in reducing the risk of sports injuries among competitive athletes.